COVID-19 Vaccines Effectiveness and Safety in Trinidad and Tobago: A Systematic Review and Meta-Analysis - Angel Justiz-Vaillant; Kimberly Roopnarine; Shaundell Solomon; Alyssa Phillips; Solange Sandy; Alyssa Subero; Sarah Seepersad; Nicholas Span; Phalmanie Ramnath; Akaasha Ramnarine; Bimala Ramdath; Chelsea Rampaul; et al. (Microorganisms)
This systematic review evaluated the effectiveness and side effects of various COVID-19 vaccines, with a focus on Trinidad and Tobago. The Pfizer-BioNTech and Moderna vaccines demonstrated the highest efficacy, particularly against COVID-19 variants, while Janssen and Sinopharm were comparatively less effective. mRNA vaccines, such as Pfizer-BioNTech and Oxford-AstraZeneca, were associated with more frequent and severe side effects, including soreness, fever, and cardiovascular issues. The review also identified significant gaps in the current scientific literature regarding COVID-19 vaccination issues in Trinidad and Tobago. These gaps highlight the need for comprehensive research to address vaccination challenges, including public health communication, equitable access, and local perceptions of vaccine safety. This analysis provides a foundation for developing targeted strategies to improve vaccine effectiveness in the region.